Health Economics Research in Cancer Screening: Research Opportunities, Challenges, and Future Directions. Issue 59 (5th July 2022) - Shih, Ya-Chen Tina; Sabik, Lindsay M; Stout, Natasha K; Halpern, Michael T; Lipscomb, Joseph; Ramsey, Scott; Ritzwoller, Debra P
Abstract: Cancer screening has long been considered a worthy public health investment. Health economics offers the theoretical foundation and research methodology to understand the demand- and supply-side factors associated with screening and evaluate screening-related policies and interventions. This article provides an overview of health economic theories and methods related to cancer screening and discusses opportunities for future research. We review 2 academic disciplines most relevant to health economics research in cancer screening: applied microeconomics and decision science. We consider 3 emerging topics: cancer screening policies in national as well as local contexts, "choosing wisely" screening practices, and targeted screening efforts for vulnerable subpopulations. We also discuss the strengths and weaknesses of available data sources and opportunities for methodological research and training. Recommendations to strengthen research infrastructure include developing novel data linkage strategies, increasing access to electronic health records, establishing curriculum and training programs, promoting multidisciplinary collaborations, and enhancing research funding opportunities.